Analisis Kesiapan Pembiayaan Hipertensi, Diabetes Melitus dan Gangguan Jiwa dalam Mendukung Program Indonesia Sehat dengan Pendekatan Keluarga (PIS PK) Tahun 2018-2020 - Astuti, Trihardini Sri Rejeki; Soewondo, Prastuti (UI Scholars Hub, 2018)
Healthy Indonesia Program with Family Approach (PIS PK) is a way to expand Puskesmas reach and access to health services through family home visit Overcoming non-communicable diseases (NCD) is a national priority in achieving Healthy Indonesia because the prevalence of NCD continues to increase. Managing NCD specifically hypertension, Diabetes Mellitus and mental disorders are among the indicators of healthy families in achieving PIS PK.This research uses the qualitative method through in-depth interviews and related document. Analysis of readiness of financing for hypertension, Diabetes Mellitus and mental is calculated using costing methode of SPM. The results indicated health spending for PIS PK activities were utilized for socialization, education and data collection. Referring to SPM costing calculation, the City of Depok was able to implement SPM for hypertension, Diabetes Mellitus and Mental Disorder with using only 1.38% of the total APBD (non-salary). Depok City is not ready in implementing PIS PK, specifically in terms of commitment, human resources, and budget. Though already familiar with PIS PK, Depok City states due to its limited resources, PIS PK implementation depends on the availability of funding from Non-Physical DAK disbursement that tends to have a lengthy lag time between the proposal process and the realization of the disbursement. The financing of PIS PK requires a more optimal planning process and allocation of human resources as needed.